Tantangan Pendidikan Agama Islam dalam Membangun Karakter Generasi Milenial - Sukari, Sukari; Haerullah, Haerullah (Lembaga Yasin AlSys, 2024)
Islamic Religious Education (PAI) plays a vital role in building the character of the millennial generation, who face significant challenges in the digital era, such as the influence of global culture, low digital literacy, and the spread of negative information on social media. This study employs a qualitative method with in-depth analysis of various literature sources and social contexts. The findings indicate that PAI can provide a strong moral foundation for young people through understanding Islamic values, fostering noble character, and increasing spiritual awareness. However, millennials often struggle to internalize religious teachings due to exposure to foreign cultures that contrast with Islamic values. Other challenges include a dependency on technology, which has the potential to reduce their mental resilience. In conclusion, adaptive strategies are needed, such as integrating technology in learning, professional development for teachers, and digital ethics education to help millennials navigate the complexities of the digital era without losing their identity and moral integrity.